Expanding the phenotype: Four new cases and hope for treatment in Bachmann‐Bupp syndrome. Issue 11 (3rd September 2021) - VanSickle, Elizabeth A.; Michael, Julianne; Bachmann, André S.; Rajasekaran, Surender; Prokop, Jeremy W.; Kuzniecky, Ruben; Hofstede, Floris C.; Steindl, Katharina; Rauch, Anita; Lipson, Mark H.; Bupp, Caleb P.
Abstract: Bachmann‐Bupp syndrome (BABS) is a rare syndrome caused by gain‐of‐function variants in the C‐terminus of ornithine decarboxylase (ODC coded by the ODC1 gene). BABS is characterized by developmental delay, macrocephaly, macrosomia, and an unusual pattern of non‐congenital alopecia. Recent diagnosis of four more BABS patients provides further characterization of the phenotype of this syndrome including late‐onset seizures in the oldest reported patient at 23 years of age, representing the first report for this phenotype in BABS. Neuroimaging abnormalities continue to be an inconsistent feature of the syndrome. This may be related to the yet unknown impact of ODC/polyamine dysregulation on the developing brain in this syndrome. Variants continue to cluster, providing support to a universal biochemical mechanism related to elevated ODC protein, enzyme activity, and abnormalities in polyamine levels. Recommendations for medical management can now be suggested as well as the potential for targeted molecular or metabolic testing when encountering this unique phenotype. The natural history of this syndrome will evolve with difluoromethylornithine (DFMO) therapy and raise new questions for further study and understanding.